Reducing Your Risk for Arthritis: The Power of Food - Sarah Curl; Jodi Fitzgerald; Danielle Nelson; Jeanette Andrade (EDIS, 2020)
Arthritis is the swelling or tenderness of the joints, and one in four adults within the United States have been diagnosed with some type of it. Arthritis can happen because of genetics and aging, but other factors, such as diet and lifestyle, may contribute to it. This new 5-page publication of the UF/IFAS Food Science and Human Nutrition Department describes the modifiable factors contributing to arthritis and tips to reduce risk for arthritis. It also includes some relevant recipe ideas. Written by Sarah Curl, Jodi Fitzgerald, Danielle Nelson, and Jeanette Andrade. https://edis.ifas.ufl.edu/fs398